The Effect of Promotion and Price on Purchasing Decisions - Reminta Lumban Batu; Cindy Monica; Bela Nadila Aprilia (Almana : Jurnal Manajemen dan Bisnis, 2020)
Indonesia with many people perfume lovers. Tiara Addict shop is a shop that sells perfume. The purpose of this research is to find out promotions, prices, purchasing decisions. In addition to determining the effect of promotion on purchasing decisions, the effect of prices on purchasing decisions and to determine the magnitude of the influence of promotions and prices on purchasing decisions perfume Tiara Addict shop. Quantitative research methods with data collection techniques through questionnaires. The results showed that promotion at Tiara Addict shop was said to be good but the promotion carried out only on one social media thus still needed to be improved even better. Prices at the Tiara Addict shop are good but there are still those that are valued according to the market price offered by consumers. The purchasing decision at the Tiara Addict shop can be said to be good but the purchasing of perfume which decreases every year results in losses. Promotion affects the purchasing decisions and the price influences the buying decision at the Tiara Addict shop, meaning that together or simultaneously the independent variable that is the promotion and price variables significantly influence The dependent variable is the purchase decision variable.